Diseño de un sistema de Control de Acceso de bajo costo para la Municipalidad de Orotina - Castillo-Jiménez, Luis Adrián (Instituto Tecnológico de Costa Rica, 2017)
The Orotina Municipality's has a service platform in which most of the procedures are performed, in this way allows the users to carry out their formalities without having to move from one department to another. This platform was recently created so people don’t know the functions of the department, because of this, visitors begin to ask in the halls and offices of the municipality. In addition, the municipal building constantly receives income from peddlers and unauthorized persons inside offices, this causes a problem of security for the employees and public, so much that robberies of the different offices have been repeated repeatedly. Therefore, is necessary to know who enters and who leaves the municipality, you want to make an access control system as a basis for improving safety and accessibility to different areas of the municipality, so that people who have permission to income they can make easily and quickly, plus there aren´t unauthorized access. It should also be able to take a photograph when you leave the building, for employees and visitors; as well as keep a report of the inputs and outputs of employees, in addition to continuing in operation in periods of power failure.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2017.
Keywords: Control; Acceso; Base de datos; Seguridad; RFID; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering